2017
DOI: 10.1089/rej.2016.1834
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia, Cardiovascular Profile, and Comorbidity in Older Men and Women: The Pro.V.A. Study

Abstract: Hyperuricemia (HU) is growing worldwide and associates with several medical conditions in the elderly. However, data about older people and possible gender differences are sparse. The aim of this study was to compare HU prevalence rates and association with relevant medical disorders in elderly subjects of both sexes. Pro.V.A. is a survey of 3099 individuals aged 65+, focusing on chronic diseases and disability. Uric acid (UA) levels were dichotomized using 6.0 mg/dL (females) and 7.0 mg/dL (males), and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…At the baseline, people with hyperuricemia had an increased frequency of several medical conditions (including obesity, diabetes mellitus, CVD, and hypertension) than those with normal SUA levels, although lower prevalence of osteoporotic fractures in both sexes. All these findings are in general agreement with the current literature regarding the topic of hyperuricemia and comorbidities . At baseline, people with hyperuricemia scored significantly worse than those with normal SUA levels in all the physical performance tests, except for handgrip strength.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…At the baseline, people with hyperuricemia had an increased frequency of several medical conditions (including obesity, diabetes mellitus, CVD, and hypertension) than those with normal SUA levels, although lower prevalence of osteoporotic fractures in both sexes. All these findings are in general agreement with the current literature regarding the topic of hyperuricemia and comorbidities . At baseline, people with hyperuricemia scored significantly worse than those with normal SUA levels in all the physical performance tests, except for handgrip strength.…”
Section: Discussionsupporting
confidence: 90%
“…SUA levels were measured using a colorimetric enzymatic method with an intra‐ and interassay coefficient of variation <10%. Hyperuricemia was defined as SUA levels ≥7 mg/dl in men and ≥6 mg/dl in women .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Age-related increase in SUA levels was found among women, in contrast, SUA level did not vary significantly among man [22]. A survey based on individuals elder than 65 years suggested the prevalence of hyperuricemia increased of only 6% in men from 65 to over 90 years, but doubled in women (from 15.3% in those having 65 years to 34.4% in the 90s) [23]. In the present study, we found the prevalence of hyperuricemia was 22.2% in the elder population, with 25.2% in male and 17.0% in female.…”
Section: Discussionmentioning
confidence: 99%